Development of directional algorithm for three-wheel omnidirectional autonomous mobile robot - Truong, Le Phuong; Liang Tsai, Huan Liang Tsai; Tuan, Huynh Cao (Vietnam Journal of Science and Technology, 2021)
A The proposed system developed an omnidirectional algorithm to control autonomous mobile robots with three wheels. The implementation system consists of three Planet DC motors with rated power of 80 W for three wheels, three encoders for speed feedback, one encoder for distance feedback, and one digital compass sensor for angle feedback. The main system with an STM32F407 microcontroller is designed for directional control of wheels based the signal received from compass sensor and encoder and then controls three subsystems to adjust the steering speed of each wheel. The sub-system is built to control only one DC motor for each wheel with the built-in proportional integral derivative controller (PID) algorithm by an STM32F103 microcontroller.  Furthermore, the directional control algorithm is developed for three omnidirectional wheels and a PID algorithm is designed to control the speed of DC motor for each wheel. From the results the proposed system has the advantages: (1) to auto adjust the angle and position; (2) to erase the sensor for tracking line of the automobile robot; (3) cost-effectiveness and high accuracy